NEDD4 Knockdown Suppresses Human Endometrial Stromal Cell Growth and Invasion by Regulating PTGS2-Mediated Ferroptosis in Endometriosis - Lao, Jianting; Hu, Panwei; Wan, Yiting; Shu, Mengmeng; Chen, Jing; Yang, Hong (Current Molecular Medicine, 2025)
BackgroundEndometriosis (EM) is a gynecological disease characterized by the benign growth of endometrial tissue outside the uterus. Upregulation of neuronally expressed developmentally downregulated 4 (NEDD4) has been reported to accelerate endometrial cancer progression.ObjectivesWe explored whether abnormal expression of NEDD4 is correlated with EM.MethodsEndometrial tissue in patients without endometriosis was used to develop the original generation of endometrial stromal cells (ESCs). Different types of endometrial tissue of patients with endometriosis were used to measure the expression of NEDD4 by immunohistochemistry (IHC) and western blotting. Its biological functions in ESCs were investigated using a cell counting kit-8 assay, fluorescein diacetate (FDA) staining, and Transwell invasion assays. Additionally, its involvement in ferroptosis was assessed by measuring Fe2+, malondialdehyde (MDA), glutathione (GSH), and reactive oxygen species (ROS) levels and the expression of ferroptosis markers.ResultsCompared with normal controls, NEDD4 levels were significantly elevated in the endometrial tissue of patients with EM. Furthermore, NEDD4 expression was higher in the ectopic endometrium than in the eutopic endometrium. NEDD4 knockdown reduced the viability and invasive capacity of ESCs, increased Fe2+, MDA, and ROS levels, and decreased GSH content. Further analysis revealed that NEDD4 knockdown promoted ferroptosis in ESCs by increasing the expression of prostaglandin-endoperoxide synthase 2 (PTGS2). As an E3 ubiquitin ligase, NEDD4 reduced PTGS2 protein levels by accelerating its ubiquitination and subsequent proteasomal degradation.ConclusionThese findings suggest that inhibiting NEDD4 reduces ESC growth and invasion in EM by regulating PTGS2-dependent ferroptosis.
Keywords: endometriosis